A Review of the Institutional Landscape for Energy Efficiency: A Case Study of Institut Teknologi Sumatera - Septi Maulidyah; Martin Muljana (Journal of Synergy Landscape, 2025)
Institut Teknologi Sumatera’s outdoor spaces have a potential contribution for solving climate change issues by providing green open spaces, with some of them become public parks. However not all of green spaces have been designed to optimize its function as a part of energy efficiency to support institutional buildings, given the reality that there is still a consumption of unrenewable energy in the buildings and lack of optimization of outdoor spaces for natural lighting and air circulation. This research aims to evaluate the energy efficiency landscaping in the existing outdoor spaces and give some recommendations to support a more sustainable campus landscape. The research method used a qualitative descriptive method where the observation taken as the primary data and literature review taken as the secondary data. The literature review would result in finding out how energy efficient landscaping should work especially in an institutional landscape and compare it to the facts found through the observation. The research results find that at macro scale there was a need to consider priority scales between building and make it more compact to minimize mobilization using vehicles as it would contribute to more carbon emission. It’s also important to manage the transportation by prioritize pedestrian-oriented design instead of car-oriented design to support the energy efficiency. At a micro scale, there was a benefit found by using shade tree such as Rain tree (Samanea saman) as a canopy adjacent to the buildings. There is also a benefit to use man-made structure or shade tree over the pathway in order to provide thermal comfort. This finding hopefully could become a consideration for designing an institutional landscape that is able to encourage energy efficiency and healthier environment.